2021
DOI: 10.19136/era.a8n1.2739
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del periodo de masculinización en la tilapia del Nilo var spring empleando 17α-metiltestosterona

Abstract: Una alternativa para reducir el uso de hormonas con aplicación inmediata en el cultivo comercial de la tilapia del Nilo, es la evaluación precisa de los tiempos de masculinización en variedades domesticadas. El objetivo del trabajo fue evaluar el porcentaje de masculinización y el crecimiento obtenido en la tilapia del Nilo alimentada con alimento comercial adicionado con 17α- metiltestosterona a diferentes tiempos. Para ello se evaluaron cinco tiempos (0, 10, 15, 20 y 25 días) de administración de hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Although the duration of hormonal treatment has been pointed out as an important factor to successfully induce high rates of sex reversal, in recent years, both feminization and masculinization experiments with Nile tilapia, have shown that it is not necessary to administer the hormone for more than 20 days after the onset of the labile period to induce high rates of sex reversal [12,42,43,44]. Nakamura and coauthors [45] reports that under the light microscope, the first signs of gonadal sex differentiation appear in Nile tilapia fry at 23-26 days after hatching with the formation of the ovarian cavity in the XX gonad or the efferent duct in the XY gonad.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the duration of hormonal treatment has been pointed out as an important factor to successfully induce high rates of sex reversal, in recent years, both feminization and masculinization experiments with Nile tilapia, have shown that it is not necessary to administer the hormone for more than 20 days after the onset of the labile period to induce high rates of sex reversal [12,42,43,44]. Nakamura and coauthors [45] reports that under the light microscope, the first signs of gonadal sex differentiation appear in Nile tilapia fry at 23-26 days after hatching with the formation of the ovarian cavity in the XX gonad or the efferent duct in the XY gonad.…”
Section: Discussionmentioning
confidence: 99%
“…Tao and coauthors [38] reports that typically, when hormonal treatment is administered during the period covering 3-6 days after hatching, phenotypic sex can be successfully reversed in both sexes. In this regard, Trejo-Quezada and coauthors [44] reports starting the steroid treatment five days after hatching in Nile tilapia (Var GIFT) and obtaining a 100% males supplying 60 mg Kg -1 of 17α-Brazilian Archives of Biology and Technology. Vol.66: e23210792, 2023 www.scielo.br/babt methyltestosterone during only 10 and 15 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that monosex, all-male Nile tilapia (Oreochromis niloticus) populations show better growth than mixed populations, eliminating unwanted reproduction and allowing the production of homogeneous size fish (Varadaraj & Pandian 1989, Mair et al 1997, Müller-Belecke & Hörstgen-Schwark 2007 Associate Editor: Mauricio Laterça Alcántar-Vázquez et al 2014) at harvest. In recent years, the production of all-male populations has been recognized as the most effective technique to increase Nile tilapia yield under commercial farming conditions (Müller-Belecke & Hörstgen-Schwark 2007, Phumyu et al 2012, Trejo-Quezada et al 2021. Currently, the most used method to achieve monosex populations is sex reversal, through the inclusion of steroids in the balanced food supplied during the fry period (Piferrer 2001, Alcántar-Vázquez 2018 before sexual differentiation, which allows obtaining a population composed of 100% male fish (Jiménez & Arredondo 2000, Daza et al 2005, Trejo-Quezada et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the production of all-male populations has been recognized as the most effective technique to increase Nile tilapia yield under commercial farming conditions (Müller-Belecke & Hörstgen-Schwark 2007, Phumyu et al 2012, Trejo-Quezada et al 2021. Currently, the most used method to achieve monosex populations is sex reversal, through the inclusion of steroids in the balanced food supplied during the fry period (Piferrer 2001, Alcántar-Vázquez 2018 before sexual differentiation, which allows obtaining a population composed of 100% male fish (Jiménez & Arredondo 2000, Daza et al 2005, Trejo-Quezada et al 2021.…”
Section: Introductionmentioning
confidence: 99%